Ethanol dry reforming for h2 production over lanthanide-group promoted Co/Al2O3 catalysts - Tai, Chan Kong (2015)
This paper presents the studies of the La-group promoter addition effects and their performances. Three different catalysts are synthesized with addition of different promoters supported by alumina. The catalysts are synthesized by using the wet impregnation process, which involved dissolving and mixing specific calculated amount of nitrate salts and calcined alumina in distilled water. The solutions are then stirred for 3 consecutive hours before they are dried in the oven for 12hrs. Lastly, the catalysts are calcined in a furnace at 1023K for 5 consecutive hours to remove remaining water content and nitrates. The calcined and uncalcined catalysts were collected for catalyst characterization analysis which involved, Thermalgrametric Analysis (TGA), Scanning Electron Microscopy (SEM), Brunauer Emmett Teller (BET) and X-ray Diffraction Analysis (XRD). Calcined unreduced catalysts were used for ethanol dry reforming syngas production reaction runs at conditions of temperature 973K, pressure 1 atm, and 1:1 C2H5OH to CO2 ratio. The content of the produced syngas were analyzed using gas chromatography, and the results were compared between the catalysts for their performances. XRD analysis showed that the second metal promotion did not affect the original structure of catalyst. The SEM analysis indicates addition of cerium and lanthanum as promoters affected the morphology of the catalyst by altering the surface texture by introducing flakes to the molecular surface of the promoted catalysts. Addition of La-group promoters is capable to provide stable catalytic performance and slightly improved C2H5OH and CH4 conversion into syngas mixture of H2 and CO when compare to non-promoted cobalt catalyst. The promoter addition decreases/slow-down the process of carbon decomposition on the catalysts’ surfaces in the order; La > Ce > non-promoted Co/Al2O3 catalysts together boosts up the production of H2 and CO gas in term of production rate, yield and also selectivity. The production output H2:CO ratio is very suitable for downstream production such as Fischer–Tropsch synthesis. The trend of CH4:CO ratio suggests catalytic reforming of methane from ethanol decomposition occurrence, where methane was converted into syngas mixture of CO and H2. The overall performances of catalysts increased by the promotion order, La > Ce > non-promoted Co/Al2O3 catalysts.